A Study to Evaluate the Effectiveness of Knowledge Regarding Self-Care in Patient of Janu-Sandhigata Vata w.s.r to Osteoarthrosis- Primary Care Base Structured Teaching Program - Kumar, Ravi; Sharma, Reetu; Sevatker, B K (International Research Journal of Ayurveda & Yoga, 2022)
Background –Knowledge about any disease is the best way of prevention of any disease. Janu sandhigta vata is the disease that occurs in old age. If we have knowledge about Janu Sandhigata vata before ongoing through the disease we have prevent this disease. So a study to evaluate the effectiveness of knowledge of self care activities in patients of Janu Sandhigata vata on out patients of National institute of Ayurveda, Jaipur. Objectives – 1. To develop and administer structured teaching program and access the knowledge of selfcare in knee Osteoarthrosis.2. To evaluate the effectiveness of Structured Teaching Program regarding selfcare among janusandhigata vata w.s.r. to Osteoarthrosis patients by comparing pre and post test knowledge score Method – Sample size is 150 of Janu Sandhigata Vata who visit the OPD of NIA, Jaipur with random sampling technique. Tool comprised of knowledge questionnaire and 3point rating i.e., inadequate, moderate, adequate knowledge. Results- In pre test adequate knowledge is 0% moderate knowledge is 34% and adequate knowledge is 66% and on post testing adequate knowledge is 94% and moderate knowledge is 6% while inadequate knowledge is 0%. The mean value of pre score is 9.973 and post score is 22.159 with mean difference is 12. 186.In paired t-test, p value is < 0.0001 suggest Extremely significant for Structured teaching programme for Janusandhigata Vata. Conclusion: - As Janu-sandhigata Vata is a Krichasadhya vyadhi, so the better option is to prevent the disease by selfcare management, Structured Teaching Program is a better approach towards the understanding of the disease and its management. Above results findings suggest that the after STP program knowledge of patient is significantly increases. Hence it suggests that, STP program is useful in increasing the knowledge of patient regarding disease.